2007
DOI: 10.1111/j.1365-2966.2007.11390.x
|View full text |Cite
|
Sign up to set email alerts
|

The 6C** sample of steep-spectrum radio sources - II. Redshift distribution and the space density of high-redshift radio galaxies

Abstract: We use the 6C * * sample to investigate the comoving space density of powerful, steep-spectrum radio sources. This sample, consisting of 68 objects, has virtually complete K-band photometry and spectroscopic redshifts for 32 per cent of the sources. In order to find its complete redshift distribution, we develop a method of redshift estimation based on the K-z diagram of the 3CRR, 6CE, 6C * and 7CRS radio galaxies. Based on this method, we derive redshift probability density functions for all the optically ide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…In the subsequent decades, the redshift cutoff problem for the steep-spectrum radio sources has always been controversial (e.g. Jarvis et al 2001;Cruz et al 2007). This situation was significantly improved when Rigby et al (2011) found a clear (at > 3σ significance) decline in the number density in steep-spectrum radio sources.…”
Section: The Redshift Cutoffmentioning
confidence: 99%
“…In the subsequent decades, the redshift cutoff problem for the steep-spectrum radio sources has always been controversial (e.g. Jarvis et al 2001;Cruz et al 2007). This situation was significantly improved when Rigby et al (2011) found a clear (at > 3σ significance) decline in the number density in steep-spectrum radio sources.…”
Section: The Redshift Cutoffmentioning
confidence: 99%
“…Larger USS samples are needed to detect more distant objects as they are more rare. However, steep-spectrum selection also misses a significant fraction of HzRGs (e.g., Jarvis et al 2009) and not all USS sources are associated with HzRGs (e.g., Jarvis et al 2001;Cruz et al 2007;van Weeren et al 2009). Therefore a combination of deep radio and optical/NIR survey data will be a more powerful way of identifying HzRGs by searching for optically/NIR faint counterparts to the radio sources (e.g., Brookes et al 2006;Ker et al 2012).…”
Section: Ultra-steep Spectrum Sourcesmentioning
confidence: 99%
“…The method developed in Cruz et al (2007) uses a model of the distribution of radio galaxies as a function of redshift together with the linear K – z relation to generate a Monte Carlo simulation of radio sources which populate a synthetic K – z diagram. The advantage of this method over simply applying a linear fit to the K – z relation is that it incorporates information about the scatter in this relation and is thus able to provide a measure of the uncertainty in the output redshift estimates.…”
Section: Estimating Redshiftsmentioning
confidence: 99%